2014
DOI: 10.1021/bc500153x
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cells Donate Electrons to Methylene Blue Mediated Chemical Reduction of Methemoglobin Compartmentalized in Liposomes in Blood

Abstract: Electron-energy-rich coenzymes in cells, NADH and NADPH, are re-energized repeatedly through the Embden-Meyerhof and pentose-phosphate glycolytic pathways, respectively. This study demonstrates extraction of their electron energies in red blood cells (RBCs) for in vivo extracellular chemical reactions using an electron mediator shuttling across the biomembrane. Hemoglobin-vesicles (HbVs) are an artificial oxygen carrier encapsulating purified and concentrated Hb solution in liposomes. Because of the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…Anesthetized healthy male Wistar rats received HbV with about 50% metHb level; then they received a dye solution. An earlier study confirmed that the reduction efficiency of MB increased with a larger injection amount in the range of 0.42-1.27 mg/kg body weight [16]. Assuming that the other dyes show similar profiles, the injection amount was fixed to 1.27 mg MB/kg body weight in this study, which is equal to approximately 4 lmol/kg body weight.…”
Section: In Vivo Reduction Of Encapsulated Methbsupporting
confidence: 66%
See 3 more Smart Citations
“…Anesthetized healthy male Wistar rats received HbV with about 50% metHb level; then they received a dye solution. An earlier study confirmed that the reduction efficiency of MB increased with a larger injection amount in the range of 0.42-1.27 mg/kg body weight [16]. Assuming that the other dyes show similar profiles, the injection amount was fixed to 1.27 mg MB/kg body weight in this study, which is equal to approximately 4 lmol/kg body weight.…”
Section: In Vivo Reduction Of Encapsulated Methbsupporting
confidence: 66%
“…After 5 min, 2.6 mM of the dye solution was injected at the dose rate of 1.53 ml dye/kg body weight. An earlier study confirmed that an increased dose of MB solution (2.6 mM) in the range 0.506-1.53 ml/kg body weight caused the most effective reduction of metHb [16]. This dosage is below the recommended maximum dosage for MB (2 mg/kg, which is approximately 2.4 ml dye/kg rat [2.6 mM]) for injection in treatment of methemoglobinemia [15].…”
Section: In Vivo Reduction Of Encapsulated Methb In Topload Infusion mentioning
confidence: 75%
See 2 more Smart Citations
“…[4][5][6][7] Especially, for the chronic blood shortage all over the world, 8 developing blood substitutes is in urgent demand, and various hemoglobin-based oxygen carriers (HBOCs) have been synthesized. In developing HBOCs, one of the most important properties is its oxygen binding behavior.…”
Section: Introductionmentioning
confidence: 99%